2021
DOI: 10.1101/2021.04.27.21255706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surging COVID-19 in Bangladesh driven by B.1.351 variant

Abstract: A dramatic resurgence of COVID-19 cases and deaths in Bangladesh in March 2021 coincided with the SARS-CoV-2 B.1.351 (501Y.V2) variant of concern rapidly becoming the dominant circulating variant. Concurrently, increasing numbers of reinfections have been detected and the effective Reproductive number, Rt, has doubled, despite high levels of prior infection in Dhaka city. These data support the prediction that acquired immunity from past infection provides reduced protection against B.1.351, and highlights the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Similar to the first wave, introduction of a lineage of the beta variant in November 2020 caused the majority of cases, suggesting that a potential superspreading event was responsible for the countrywide spread. 5 Leading up to the second wave, mobility indicators bounced back to above baseline, suggesting that the COVID-19 threat was considered less serious by the population after the first wave. In response, the Government of Bangladesh announced a second round of travel restrictions that had a strong impact on mobility but stopped short of a nationwide strict lockdown.…”
Section: Successive Waves Caused By New Variantsmentioning
confidence: 99%
“…Similar to the first wave, introduction of a lineage of the beta variant in November 2020 caused the majority of cases, suggesting that a potential superspreading event was responsible for the countrywide spread. 5 Leading up to the second wave, mobility indicators bounced back to above baseline, suggesting that the COVID-19 threat was considered less serious by the population after the first wave. In response, the Government of Bangladesh announced a second round of travel restrictions that had a strong impact on mobility but stopped short of a nationwide strict lockdown.…”
Section: Successive Waves Caused By New Variantsmentioning
confidence: 99%
“…In particular, during the first months of the pandemic, residents in Dhaka, the country’s largest and most populated city, had easier access to SARS-CoV-2 testing compared to other regions in Bangladesh [14,57]. Consequently, the Dhaka division reported the majority (50.5%) of confirmed SARS-CoV-2 cases in the country (Figure 2A) [14,57]. Spikes in reported cases during the first wave of the pandemic were observed in some other divisions, e.g., in Rangpur in the start of July 2020 (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that rising cases could be somewhat driven by increased testing capacity over time [14]. In particular, during the first months of the pandemic, residents in Dhaka, the country's largest and most populated city, had easier access to SARS-CoV-2 testing compared to other regions in Bangladesh [14,57]. Consequently, the Dhaka division reported the majority (50.5%) of confirmed SARS-CoV-2 cases in the country (Figure 2A) [14,57].…”
Section: Epidemiological Findingsmentioning
confidence: 99%
“…Another study conducted in the United States revealed an effective reproduction number (R t ) between 1 and 2 in most states [175]. In Bangladesh, the effective reproduction number for the B.1.351 variant was estimated to be 3.5 [176]. There is a scarcity of information concerning the Beta reproduction number.…”
Section: Viral Loadmentioning
confidence: 99%